Epitopes on the S1 subunit of pertussis toxin recognized by monoclonal antibodies. - Kim, K J (1989)
To identify the neutralizing epitopes on the S1 subunit (A promoter) of pertussis toxin, we characterized anti-S1 monoclonal antibodies (MAbs) X2X5, 3CX4, and 6FX1. We confirmed by immunoblot analysis that these MAbs bind to the S1 subunit and not to the B oligomer of pertussis toxin and that they recognize different epitopes by a competitive binding enzyme-linked immunosorbent assay. These MAbs had differential abilities to neutralize the lymphocytosis-promoting factor activity of pertussis toxin in mice: 3CX4 and 6FX1 had partial neutralizing abilities, while MAb X2X5 had none. With these MAbs, the epitopes on the S1 subunit were examined by using trypsinized S1 peptides, recombinant truncated S1 molecules, and synthetic peptides. The non-neutralizing MAb X2X5 bound in immunoblots to tryptic peptides of various sizes as small as 1.5 kilodaltons; the neutralizing MAbs 3CX4 and 6FX1 bound only to a 24-kilodalton tryptic peptide band. Immunoblot studies with recombinant truncated S1 molecules demonstrated that amino acid residues 7 to 14 and 15 to 26 play an important role in the binding of neutralizing MAbs and the non-neutralizing MAb, respectively. The binding of these MAbs was not dependent upon the presence of C-terminal amino acid residues 188 to 234. To further define B-cell epitopes, the binding of the MAbs we tested to synthetic peptides representing the entire S1 subunit were examined. Neutralizing MAbs 3CX4 and 6FX1 bound to none of these peptides, further suggesting that these MAbs recognize conformational epitopes. The non-neutralizing MAb X2X5 bound to peptides 11 to 26 and 16 to 30, demonstrating that the major antigenic determinant recognized by this MAb is a linear epitope located within residues 16 to 26.